WORKPLACE, WORKLOAD AND STRESS MANAGEMENT IN A PUBLIC ORGANISATION: A CASE STUDY OF UNIVERSITY OF PORT HARCOURT TEACHING HOSPITAL, RIVERS STATE - Orlu Chukwuemeka, Ph.D (European Journal of Humanities and Educational Advancements, 2023)
The role of workplace environment, workload, and stress management in influencing organizational performance remains unequivocally critical. Stress, a multifaceted phenomenon, functions as a catalyst for divergence from normal psychological or physiological functioning. Its etiology can be categorized into external stressors, which are typically environmental or psychological in nature, and internal stressors, frequently precipitated by medical conditions or procedures. Stress in a workplace context manifests in myriad forms, including generalized stress, as well as emotional and social strains. A predominant catalyst for occupational stress arises from incongruities between workload and the employee’s skill set, leading either to overburdening or underutilization, both of which contribute to fatigue and stress. To empirically scrutinize these dynamics, the present study employed a dual-hypothesis framework. Questionnaires, predicated on a four-tiered Likert scale—Strongly Agree, Agree, Disagree, and Strongly Disagree—were disseminated across the six departments of University of Port Harcourt Teaching Hospital. In total, 160 of the 130 administered questionnaires were completed and returned. Data analysis was executed through the application of Z-test for mean comparisons. The findings of the study resoundingly reject the null hypotheses, underlining the integral connection between workload, stress, and organizational performance. Consequently, the study proffers managerial recommendations, notably advocating for supervisors to engage in open dialogues with subordinates concerning task allocation, completion timelines, and associated work pressures. Such consultative approaches are posited as essential for mitigating stress and enhancing overall productivity within the organization